REVIEW OF THE PHYSICAL CONDITION OF FEMALE ROWING ATHLETES IN KUANTAN SINGINGI DISTRICT - Rati Lanosiansa; Aref Vai; Ali Mandan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the physical condition of female rowing athletes in Kuantan Singingi Regency. This study is a study with a quantitative descriptive approach, because the data is presented in the form of numbers and analyzed based on statistical analysis. The sample in this study was 9 female rowing athletes from Kuantan Singingi Regency. The instruments in this study were physical ability tests for sports, namely sit and reach tests, abdominal muscle endurance measurements, arm muscle endurance measurements, VO2MAX measurements, power tests and measurements or explosive power tests. Data analysis will be analyzed using descriptive statistics in the form of frequency tabulation by describing the research results obtained from various test measurements of the level of physical condition. The results showed that: Abdominal and arm muscle endurance still needs improvement because abdominal muscle endurance is 44.4% in the "good and less" category. Arm muscle endurance with the majority of athletes in the "moderate" category of 44.4%. While leg muscle endurance showed very good results with a large percentage of 88.8%. Then, the flexibility of athletes is mostly in the "good" category. And VO2MAX endurance with the majority in the "less" category of 66.6% to the "very less" category with a large percentage of 33.3%. It can be concluded that the physical condition of female rowing athletes in Kuantan Singingi Regency must be improved again.